Evaluation of the relative expression of genes associated with adherence after different hours of co-culture between Streptococcus uberis and MAC-T cells - Fessia, Alumine Soledad (2021)
Streptococcus uberis is an environmental pathogen associated with subclinical and clinical IMI in both lactating and non-lactating cows. RC19 strain was isolated from a cow with subclinical mastitis, qualitatively classified as moderate biofilm producer in Todd Hewitt medium (THB), and it showed a high value of the adhered bacteria (CFU/ml). Hence, the aims of this study were (a) to determine ability to adhere to and internalize into epithelial cells MAC-T for 1, 2 and 3 h, (b) to evaluate the relative expression of adherence-associated genes from co-cultures of S. uberis with MAC-T cells at 1, 2 and 3 h. We hypothesized that upon contact with bovine mammary epithelial cells, S. uberis upregulates adherence-associated genes encoding adhesins, which enable it a higher adherence to and/or internalization into host cells. Four to six genes increased their R with regard to the control after initial contact with MAC-T cells (group 1) at 1, 2 and 3 h. The highest value of R was observed at 2 h after co-culture between RC19 and MAC-T cells.